RESEARCH REGARDING THE MODAL PARAMETERS IDENTIFICATION FOR METALLIC STRUCTURES (I) - Dan ILINCIOIU; Ion TĂTARU; Cosmin-Mihai MIRIŢOIU (Fiabilitate şi Durabilitate)
In this paper, starting from previous methods written by other authors, we present the theoretical background of the modal identification for hyperstatic metallic structures (in an own way). We present also the known methods which are used nowadays for modal parameters identification.